Associação entre β-cariofileno e pregabalina apresenta ação anticonvulsivante aguda em modelo de crises epilépticas induzidas por pentilenotetrazol em ratos - Sobral, Karine Gabriela da Costa (2021)
Epilepsy is a chronic neurological disease characterized by recurrent seizures. However, current anticonvulsants are ineffective in nearly a third of patients and can cause adverse effects. Beta-caryophyllene is agonist of type 2 cannabinoid receptors, which exhibits antioxidant, anti-inflammatory and neuroprotective activities. Pregabalin is an anticonvulsant used as an adjunct in the treatment of epilepsy. Given the fact that drug resistance is increasingly frequent in patients with epilepsy, we tested the hypothesis that the beta-caryophyllene associated with pregabalin exhibits anticonvulsant effect in a model of acute seizures induced by pentylenetetrazol (PTZ) in rats. Furthermore, the possible neuroprotective effect of the pharmacological association in the frontal cortex were evaluated. For this purpose, adult male Wistar rats were connected to the electroencephalogram equipment, where they received the following treatments: (i) beta-caryophyllene 100 mg / kg, i.p.; (ii) pregabalin 40 mg / kg, i.p.; (iii) PTZ 60mg / kg, i.p.; and/or their vehicles with a 30-minute interval between each administration and observed for 15 minutes after the last treatment. Latency for myoclonic, tonic-clonic seizures, duration and seizure score were measured. Our results demonstrated that beta-caryophyllene in combination with pregabalin increases the latency to onset of PTZ-induced myoclonic and tonic-clonic seizures, as well as reducing the duration and score of these crises. These data were corroborated by the electroencephalographic recording. Regarding molecular analyses, PTZ-induced seizures caused a reduction in the Nuclear Factor erythroid 2-related factor 2 (Nrf2) levels, which was not prevented by the combined treatment of beta-caryophyllene with pregabalin. Of note, decreased levels of glial fibrillary acidic protein (GFAP), c-Fos and 3-NT was observed in animals that received both treatments. These results are possibly due to an addition-type interaction between both substances. However, additional studies are examined to investigate how clinical these findings are, as well as their underlying components.